The Relationship Between Behavior Toward Breast Self-Examination as Early Detection of Breast Cancer in Adolescent Girls at Bali Dewata Health High School - Ni Nyoman Putri Asri Rahmasari; I Ketut Gama; I Gusti Ketut Gede Ngurah; Ketut Sudiantara; Komang Ayu Henny Achjar; Agus Sri Lestari; I Wayan Suardana; I Wayan Mustika; I Gusti Ayu Harini; Ni Nyoman Hartati (Health Dynamics, 2025)
Background: Adolescence is a critical period for establishing preventive health behaviors. Breast self-examination (BSE/SADARI) is an effective and low-cost method for early breast cancer detection. However, awareness and practice among Indonesian adolescents remain low, contributing to delayed diagnoses. This study aimed to analyze the relationship between knowledge, attitude, and practice toward BSE and early detection outcomes among adolescent girls at Bali Dewata Health Vocational School. Methods: A cross-sectional analytic study was conducted among 71 female students selected through proportional random sampling. Data were collected using validated questionnaires assessing knowledge, attitude, and practice regarding BSE, and categorized SADARI results into low, medium, and high risk. Statistical analysis was performed using chi-square tests (p < 0.05). Results: The majority of respondents were classified as low risk (39.4%), followed by medium (32.4%) and high risk (28.2%). Knowledge level showed a significant association with SADARI results (p = 0.000), with higher knowledge correlating with lower risk. Practice was also significantly associated (p = 0.045), while attitude showed no significant relationship (p = 0.090) but indicated a positive trend. Conclusion: Knowledge and regular BSE practice are key determinants of early breast cancer detection among adolescents. Integrating structured breast health education into school programs is recommended to improve preventive behaviors and reduce future breast cancer risk.